Concise Review: Functional Definition of Endothelial Progenitor Cells: A Molecular Perspective. (5th July 2016) - Patel, Jatin; Donovan, Prudence; Khosrotehrani, Kiarash
Abstract : Notch signaling driving the quiescence of progenitors has been shown to be central to progenitor self-renewal. This new molecular definition has tremendous translational consequences because progenitors have been shown to display greater vasculogenic potential. This molecular definition of endothelial progenitor cell (EPC) self-renewal allows assessment of the quality of presumed EPC preparations. Abstract : : Since the discovery of endothelial progenitor cells (EPCs) almost 2 decades ago, there has been great hope in their use in treating chronic ischemic disease. Unfortunately, to date, many of the clinical trials using EPCs have been hampered by the lack of clear definition of this cell population. Attributes of a progenitor population are self-renewal and multipotentiality. Major progress has been achieved moving from a definition of EPCs based on a candidate cell surface molecule to a functional definition based essentially on self-renewal hierarchy of endothelial colony-forming cells (ECFCs). More recent work has seized on this functional characterization to associate gene expression signatures with the self-renewal capacity of ECFCs. In particular, Notch signaling driving the quiescence of progenitors has been shown to be central to progenitor self-renewal. This new molecular definition has tremendous translational consequences, because progenitors have been shown to display greater vasculogenic potential. Also, this molecular definition of EPC self-renewal allows assessment of the quality of presumed EPC preparations. This promises to be the initial stage in progressing EPCs further into mainstream clinical use. Significance : The development of a therapy using endothelial progenitor cells provides great hope for patients in treating cardiovascular diseases going forward. For continual development of this therapy toward the clinical, further understanding of the fundamental biology of these cells is required. This will enable a greater understanding of their stemness capacity and provide insight into their ability to differentiate and drive tissue regeneration when injected into a host.